Načrtovanje in optimiranje avtomatiziranih regalnih skladiščnih sistemov - Lerher, Tone (Strojniški vestnik, 2006)
In this paper a model for the design and optimization of an automated storage-and-retrieval system for single- and multi-aisle systems is presented.Because of the required conditions, i.e., that the warehouse should be technically highly efficient and that it should be designed at reasonable expense, the objective function is represented by minimum total costs. The objective function combines elements of the static and dynamic parts of the warehouse, the investment, and the operational costs of the warehouse. Due to the non-linear, multi-variable and discrete shape of the objective function, the method of genetics algorithms was used for the optimization process of thedecision variables. An analysis of the chosen automated warehouse with two types of the single- and multi-aisle automated storage and retrieval systems is presented. It was established that the optimum solutions regarding total costs of the warehouse can be found in the area of high and long storage racks. Consequently, this influences the reduction of the number of picking aisles and the number of storage and retrieval machines. The results of the analysis show that the choice of a type of single- or multi-aisle system depends crucially on the required throughput capacity of the warehouse. The presented model is a very useful and flexible tool for choosing a particular type of single- or multi-aisle system when designing automated warehousing systems.
Keywords: skladišča; avtomatizacija; načrtovanje; optimiranje